Improvement of energy metabolism associated with NUTRIOSE® soluble fiber, a dietary ingredient exhibiting prebiotic properties, requires intestinal gluconeogenesis. (May 2023) - Vily-Petit, Justine; Soty, Maud; Silva, Marine; Micoud, Manon; Bron, Clara; Guérin-Deremaux, Laetitia; Mithieux, Gilles
Graphical abstract: Highlights: NUTRIOSE exerts metabolic benefits in mice. NUTRIOSE moderates body weight gain and hepatic steatosis under high calorie diet. NUTRIOSE activates browning of the subcutaneous white adipose tissue. NUTRIOSE increases the genetic diversity of the gut microbiota. The metabolic benefits of Nutriose require intestinal gluconeogenesis. Abstract: While the prevalence of obesity progresses worldwide, the consumption of sugars and dietary fiber increases and decreases, respectively. In this context, NUTRIOSE® soluble fiber is a plant-based food ingredient with beneficial effects in Humans. Here, we studied in mice the mechanisms involved, particularly the involvement of intestinal gluconeogenesis (IGN), the essential function in the beneficial effects of dietary fibers. To determine whether NUTRIOSE® exerts its beneficial effects via the activation of IGN, we studied the effects of dietary NUTRIOSE® on the development of obesity, diabetes and non-alcoholic fatty liver disease (NAFLD), which IGN is able to prevent. To assert the role of IGN in the observed effects, we studied wild-type (WT) and IGN-deficient mice. In line with our hypothesis, NUTRIOSE® exerts metabolic benefits in WT mice, but not in IGN-deficient mice. Indeed, WT mice are protected from body weight gain and NAFLD induced by a high calorie diet. In addition, our data suggests that NUTRIOSE® may improve energy balance by activating a browning process in subcutaneous white adipose tissue. While the gut microbiota composition changes with NUTRIOSE®, this is not sufficient in itself to account for the benefits observed. On the contrary, IGN is obligatory in the NUTRIOSE® benefits, since no benefit take place in absence of IGN. In conclusion, IGN plays a crucial and essential role in the set-up of the beneficial effects of NUTRIOSE®, highlighting the interest of the supplementation of food with healthy ingredients in the context of the current obesity epidemic.